Determinants of Profitability in State-Owned and Privately-Owned Banks in Indonesia: The Role of Credit Risk, Liquidity Risk, Operational Efficiency, and Green Banking - Euro Ellytra; Umi Widyastuti; Gatot Nazir Ahmad (International Journal Labs, 2026)
This research examines the effects of credit risk, liquidity risk, operational efficiency, and green banking on the profitability of state-owned (Badan Usaha Milik Negara or BUMN) and privately owned national (Badan Usaha Milik Swasta or BUMS) commercial banks listed on the Indonesia Stock Exchange during the 2020–2024 period. Credit risk is measured using the Non-Performing Loan (NPL) ratio, liquidity risk is measured using the Loan-to-Deposit Ratio (LDR), operational efficiency is measured using the Operating Expenses to Operating Income (BOPO) ratio, and green banking is measured based on the level of sustainable banking implementation, while profitability is proxied by the Net Interest Margin (NIM). This quantitative descriptive-verificative study uses secondary data obtained from annual reports and audited financial statements. The sample consists of 14 banks selected through purposive sampling during the 2020–2024 period, resulting in 70 panel observations analyzed using panel data regression with EViews 9. The Random Effects Model (REM) was selected as the most appropriate model based on the Chow, Hausman, and Lagrange Multiplier tests and fulfilled the requirements of classical assumption testing. The results show that NPL has a negative and significant effect on NIM, whereas LDR has a positive and significant effect. Conversely, BOPO and green banking have no significant effect on NIM. Simultaneously, the four independent variables do not have a significant effect on profitability, with an Adjusted R² value of only 6.84 percent. State-owned banks also outperformed privately owned banks across all six indicators examined. These findings indicate that effective credit risk and liquidity management remain key determinants of banking profitability, while the benefits of green banking are more likely to emerge over the long term. The findings provide valuable insights for bank management, regulators, and future researchers.